1995
DOI: 10.1007/bf00168885
|View full text |Cite
|
Sign up to set email alerts
|

Wound management in burn centres in Europe

Abstract: Infection remains a common cause of death in burned patients. A recent survey of UK burns units showed a range of opinion on the timing of burn wound excision and the use of therapeutic and prophylactic antibiotics. The same questionnaire was sent to other European burns units to assess their practice. Answers were obtained from 96 of the 164 units contacted. A written policy on antibiotic treatment was used by 35 (36%) units, imipenem being the single most popular antibiotic, but courses often lasted more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…To date, silver sulfadiazine (SSD) 1% cream is the most commonly used local treatment for burns. 22,23 Its popularity stems from the fact that prior studies have demonstrated the ability of SSD to reduce bacterial contamination, 24 to speed the rate of re-epithelialization of wounds, 25 and to retard wound contracture. 25 Tissue adhesives, such as the cyanoacrylates, have been available outside the United States for many years.…”
mentioning
confidence: 99%
“…To date, silver sulfadiazine (SSD) 1% cream is the most commonly used local treatment for burns. 22,23 Its popularity stems from the fact that prior studies have demonstrated the ability of SSD to reduce bacterial contamination, 24 to speed the rate of re-epithelialization of wounds, 25 and to retard wound contracture. 25 Tissue adhesives, such as the cyanoacrylates, have been available outside the United States for many years.…”
mentioning
confidence: 99%
“…13,14 In the treatment of patients with superficial partialthickness burns, SSD was shown to reduce bacterial contamination, speed re-epithelialization of wounds, and retard wound contracture. 1 Biafine is an oil-inwater emulsion containing alginate that may be used in the treatment of superficial partial-thickness burns. Biafine has been shown to be chemotactic for macrophages and to increase IL-1/IL-6 ratio in suction blister wounds in human volunteers, 9 suggesting that it may have a role as an anti-inflammatory agent for treatment for cutaneous wounds.…”
Section: Discussionmentioning
confidence: 99%
“…A commonly used local treatment for burns is silver sulfadiazine 1% cream (SSD). 1 Previous studies have shown that SSD reduces bacterial contamination, speeds re-epithelialization of wounds, and retards wound contracture. [2][3][4][5][6][7][8] Biafine (Labortoires Medix, Houdan, France) is an oil-in-water emulsion containing alginate, which may be used in the treatment of superficial partial-thickness burns.…”
mentioning
confidence: 99%